Ministry of Trade and Industry Decree No. 405 of the Year 2022 = وزارة التجارة والصناعة قرار رقم 405 لسنة 2022 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic